The Longitudinal Study of Australian Children: Latest information. - Soloff, C (My University, 2007)
In 2004, more than 10,000 children and families around Australia agreed to take part in Growing Up in Australia, the longitudinal study of Australian children (LSAC). This study involves two representative cohorts of children - approximately 5,000 infants and 5,000 children aged 4-5 years in 2004. The study is following the development of these children until at least 2010, returning to the children and their families every two years. Two waves of interviewing have now been completed, with data from the second wave due for release in the second half of 2007. Growing Up in Australia is a major data resource for researchers and policy makers. The study collects information about many aspects of children's development - physical and mental health, social adjustment, cognitive development, and school achievement - and their experiences at home, in child care, at school and in local communities. Socio-economic and other contextual information is also collected. This paper provides an update on Growing Up in Australia, including an overview of the longitudinal data. Changes that have happened to the families will be outlined and an indication will be given of how the children are progresing since they joined the study.
Keywords: Surveys and Survey Methodology; Surveys and Survey Methodology; Surveys and survey methodology; Surveys and Survey Methodology; Surveys and Survey Methodology